The impact of positive feedback on student outcomes and perceptions. Issue 2 (17th February 2022) - Faulconer, Emily; Griffith, John; Gruss, Amy
Abstract: High quality feedback on assessments and deliverables is vital to student success. This pilot study sought to understand the impact of combining positive and performance-gap feedback in an immediate feedback scenario where students were provided multiple attempts to complete an assignment. 176 online undergraduate students were surveyed after completing a general inorganic chemistry course. Some students were provided performance-gap feedback, while others were provided performance-gap and positive feedback. The results suggest that type of feedback provided does not change students' perceptions and self-reported behaviors in the course. However, students who were provided both performance-gap and positive feedback received an average of an entire letter grade higher than the students who received only performance-gap feedback. These findings support the idea that a combination of feedback has a direct positive impact on students in an online setting.